Ultrasound characteristics of endometrial cancer as defined by International Endometrial Tumor Analysis (IETA) consensus nomenclature: prospective multicenter study. (4th June 2018) - Epstein, E.; Fischerova, D.; Valentin, L.; Testa, A. C.; Franchi, D.; Sladkevicius, P.; Frühauf, F.; Lindqvist, P. G.; Mascilini, F.; Fruscio, R.; Haak, L. A.; Opolskiene, G.; et al.
ABSTRACT: Objective: To describe the sonographic features of endometrial cancer in relation to tumor stage, grade and histological type, using the International Endometrial Tumor Analysis (IETA) terminology. Methods: This was a prospective multicenter study of 1714 women with biopsy‐confirmed endometrial cancer undergoing standardized transvaginal grayscale and Doppler ultrasound examination according to the IETA study protocol, by experienced ultrasound examiners using high‐end ultrasound equipment. Clinical and sonographic data were entered into a web‐based database. We assessed how strongly sonographic characteristics, according to IETA, were associated with outcome at hysterectomy, i.e. tumor stage, grade and histological type, using univariable logistic regression and the c ‐statistic. Results: In total, 1538 women were included in the final analysis. Median age was 65 (range, 27–98) years, median body mass index was 28.4 (range 16–67) kg/m 2, 1377 (89.5%) women were postmenopausal and 1296 (84.3%) reported abnormal vaginal bleeding. Grayscale and color Doppler features varied according to grade and stage of tumor. High‐risk tumors, compared with low‐risk tumors, were less likely to have regular endometrial–myometrial junction (difference of −23%; 95% CI, −27 to −18%), were larger (mean endometrial thickness; difference of +9%; 95% CI, +8 to +11%), and were more likely to have non‐uniform echogenicity (difference of +7%; 95% CI, +1 to +13%), a multiple, multifocal vessel pattern (difference of +21%; 95% CI, +16 to +26%) and a moderate or high color score (difference of +22%; 95% CI, +18 to +27%). Conclusion: Grayscale and color Doppler sonographic features are associated with grade and stage of tumor, and differ between high‐ and low‐risk endometrial cancer. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.